Market failure - Ramesh, Sangaralingam (Henry Stewart Talks, 2019)
Market failure, Social efficiency, Pareto efficiency, Deadweight loss, Consumer surplus, Producer surplus, Market competition, Labour market failure, Unstable commodity prices, Externalities, Asymmetric information